2018
DOI: 10.37358/rc.18.3.6167
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ELISA and PCR in Identifying Correlations between Viral Infection and Benign Prostatic Hypertrophy

Abstract: Benign prostatic hyperplasia (BPH) is induced by a persistent local inflammatory process that leads to cell proliferation. Viral infections associated with immune deficiencies can trigger the chronic inflammation of the prostate. Therefore, we have investigated several viral expressions in BPH patients and tried to establish a link with the diagnosed hyperplasia. 50 patients with BPH without urinary tract infection were tested for the presence of the following viruses: human papilloma virus (HPV), cytomegalov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Vaccine schedule includes a single dose, followed by a second dose 1-2 months later and afterwards a final dose 6 months later (63)(64)(65)(66)(67)(68). Current recommendation regarding male vaccination from CDC Advisory Committee on Immunization Practices are as follows: routine male vaccination beginning at the age of 11 or 12 years with either the quadrivalent or 9-valent vaccine, also vaccination for males aged between 13 and 21, who have not completed a three-dose cycle.…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 99%
“…Vaccine schedule includes a single dose, followed by a second dose 1-2 months later and afterwards a final dose 6 months later (63)(64)(65)(66)(67)(68). Current recommendation regarding male vaccination from CDC Advisory Committee on Immunization Practices are as follows: routine male vaccination beginning at the age of 11 or 12 years with either the quadrivalent or 9-valent vaccine, also vaccination for males aged between 13 and 21, who have not completed a three-dose cycle.…”
Section: Prevention Of Hpv Infection In Menmentioning
confidence: 99%
“…However, in high-risk patients, the early biochemical recurrence seems to increase the risk of mortality, this being the result of disease progression and metastases. It is known that high PSA values before surgery, the presence of positive surgical margins, pathological stage and other factors are predictors of biochemical recurrence (34)(35)(36)(37)(38)(39). It has been demonstrated that in patients with positive surgical margins, the tumor grade at the site of the positive margin has prognostic value and that the Gleason score of the radical prostatectomy specimen is associated with PSA velocity (40).…”
Section: Discussionmentioning
confidence: 99%
“…New applications of this medication include benign prostate hyperplasia and chronic prostatitis, with contradictory results (29,30). Jhang and Kuo (31), in their study, reviewed all current applications of this medication.…”
Section: Studies Of Efficiencymentioning
confidence: 99%